1997
DOI: 10.1159/000127255
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Experience Reduces Haloperidol-lnduced Prolactin Secretion in Female Rats

Abstract: The present study examined possible changes in the dopaminergic regulation of prolactin (PRL) secretion which have been reported to occur in reproductively experienced female rats. In the first experiment, female rats which had raised a litter to weaning and age-matched nulliparous controls were ovariectomized and challenged sequentially 2 days apart with a low (0.2 mg/kg) and high (1.0 mg/kg) dose (intravenously) of haloperidol (HAL), a dopamine antagonist. Blood samples were collected via intra-atrial cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
4
22
0
3
Order By: Relevance
“…1 B and D, respectively). These data confirmed and expanded the notion that the reproductive experience modulated the dopaminergic tone (Bridges et al, 1993;Felicio et al, 1996;Bridges et al, 1997;Hucke et al, 1998Hucke et al, , 2001Byrnes et al, 2001;Sider et al, 2003;. A similar effect was observed in DA response to haloperidol, although the drug was not supposed to produce an increase in DA levels (P<0.05; Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…1 B and D, respectively). These data confirmed and expanded the notion that the reproductive experience modulated the dopaminergic tone (Bridges et al, 1993;Felicio et al, 1996;Bridges et al, 1997;Hucke et al, 1998Hucke et al, , 2001Byrnes et al, 2001;Sider et al, 2003;. A similar effect was observed in DA response to haloperidol, although the drug was not supposed to produce an increase in DA levels (P<0.05; Fig.…”
Section: Resultssupporting
confidence: 82%
“…Reproductive experience also reduces the sensitivity of nonlactating women to the PRL-releasing actions of dopamine antagonist, metoclopramide (Del los Monteros, 1991). The same effect is demonstrated in rats after haloperidol injection (Bridges et al, 1997). These findings have demonstrated that the reproductive experience alters the female's sensitivity to a dopamine antagonist in regulating PRL secretion.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Higher doses of opiates are needed to obtain a drug-induced disruption of maternal behavior in experienced animals. Both basal and drug-induced increases of plasma prolactin levels are lower in cycling parous than in age-matched virgin rats (7,8). Similarly, both opioid-induced release and suckling-stimulated prolactin release are less intense in multiparous than in primiparous rats (4).…”
mentioning
confidence: 87%
“…These influences have been demonstrated in various physiological states (7). Particularly during pregnancy, a previous reproductive experience induces changes in both endocrine and neurochemical profile (8,9).…”
mentioning
confidence: 99%